Integrated Cognitive and Neuromotor Rehabilitation in Multiple Sclerosis: A Pragmatic Study - Barbarulo, Anna M.; Lus, Giacomo; Signoriello, Elisabetta; Trojano, Luigi; Grossi, Dario; Esposito, Mariateresa; Costabile, Teresa; Lanzillo, Roberta; Saccà, Francesco; Morra, Vincenzo Brescia; Conchiglia, Giovannina (Frontiers in Behavioral Neuroscience, 2018)
Background: Few studies examined the effects of combined motor and cognitive rehabilitation in patients with multiple sclerosis (MS). The present prospective, multicenter, observational study aimed to determine the efficacy of an Integrated Cognitive and Neuromotor Rehabilitation (ICNR) programme versus a traditional neuromotor training on walking, balance, cognition and emotional functioning in MS patients. Methods: 63 MS patients were selected and assigned either to the Integrated Treatment Group (ITG; n=32), receiving neuropsychological treatment (performed by ERICA software and paper-pencil tasks) complemented by conventional neuromotor rehabilitation, or to the Motor Treatment Group (MTG; n=31) receiving neuromotor rehabilitation only. The intervention included two 60-min sessions per week for 24 weeks. At baseline and at end of the training all patients underwent a wide-range neuropsychological, psychological/emotional and motor assessment. Results: At baseline the two groups did not differ for demographic, neuropsychological, psychological/emotional and motor features significantly. After rehabilitation, only ITG group significantly improved (p< 0.05) on test tapping spatial memory, verbal learning, attention and executive functions, as well as on scales assessing depression and motor performance (balance and gait). A regression analysis showed that neuropsychological improvement was not related to improvements in anxiety, fatigue and depression. Conclusions: The present study demonstrated positive effects in emotional, motor and cognitive aspects in MS patients who received an integrated cognitive and neuromotor training. Overall, results are supportive of interventions combining motor and cognitive training for MS